INTERPRETASI MAKNA TEKS KELONG KARYA KEMBONG DAENG DALAM POSTINGAN MEDIA SOSIAL FACEBOOK (KAJIAN SEMANTIK) - Halima, Sitti; Daeng, Kembong; Rahim, Abd (Journal Studies in Indonesian Language and Literature, 2024)
The purpose of this study is to reveal the denotative meaning and connotative meaning contained in the kelong text through Facebook social media posts. This research uses descriptive qualitative method. The research focuses only on the denotative meaning and connotative meaning of kelong text. The data collection techniques used are reading techniques and transliteration techniques. The results showed that there are 23 words or groups of words that have denotative meaning. The denotative meaning consists of: nipakrisi, annulung, pikkiri, sipammanakang, abbarajuang akkareso tojeng-tojeng, ukurik sai, akminasa, masunggu, assikola, bosi, sidakka, sare, accinik anu bajik, ampena punna tubajik, pallalangang, ri lino, passare, dasi na dasi, akgauk bajik, anatta, sarenna, tau towa siagang assalak. In addition, four sentences with connotative meanings were found. The connotative meaning consists of: lekbak labba lekbak tekne na bangkenga cinik tena nappada jappa, kallitta kuciniki na kallikku ta kucinik iyamintu gigi na toli, nitutusiang sikali eroki nipintallungi siagang nitutusiang sikali eroki nipinruangi.